2014
DOI: 10.1038/mp.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and serotonin signaling during two sensitive developmental periods differentially impact adult aggressive and affective behaviors in mice

Abstract: Pharmacologic blockade of monoamine oxidase A (MAOA) or serotonin transporter (5-HTT) has antidepressant and anxiolytic efficacy in adulthood. Yet, genetically conferred MAOA or 5-HTT hypo-activity is associated with altered aggression and increased anxiety/depression. Here we test the hypothesis that increased monoamine signaling during development causes these paradoxical aggressive and affective phenotypes. We find that pharmacologic MAOA blockade during early postnatal development (P2-P21) but not during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 68 publications
5
116
0
1
Order By: Relevance
“…The extension of the active period in 5-HT-depleted mice described by Whitney et al (2016) confirms the role of 5-HT in maintaining the normal circadian rhythm (Ciarleglio et al, 2011). Interestingly, Whitney et al (2016) also found that 5-HT depletion suppressed breaks during nocturnal activity (siestas).…”
Section: Fl/ϫsupporting
confidence: 54%
See 3 more Smart Citations
“…The extension of the active period in 5-HT-depleted mice described by Whitney et al (2016) confirms the role of 5-HT in maintaining the normal circadian rhythm (Ciarleglio et al, 2011). Interestingly, Whitney et al (2016) also found that 5-HT depletion suppressed breaks during nocturnal activity (siestas).…”
Section: Fl/ϫsupporting
confidence: 54%
“…The hyperactive phenotype reported by Whitney et al (2016) in 5-HT-depleted mice was not accompanied by changes in anxiety-like behavior in the open field, elevated plus maze, and light/dark box tests. This finding is surprising, considering that genetic and pharmacological mouse models targeting the 5-HT transporter (Kalueff et al, 2007), specific 5-HT receptors (Ramboz et al, 1998), or 5-HT depletion (Näslund et al, 2013), have consistently shown alterations in anxiety-like behavior.…”
Section: Fl/ϫmentioning
confidence: 73%
See 2 more Smart Citations
“…Supported by the affect that is experienced from the outburst of the innermost emotion (Henry, 1996), supported by that which the observation of an X-ray can tell us what from there results for a flesh (Henry, 2000, p. 317), supported by an affection that translates into a protein with implications to memory (Teixeira & Martins, 2006, p. 321-233), or in the creation of an enriched environment that favors a certain morphology of neurons with implications to the quality of life of an Alzheimer patient or in the determination of human development periods that are more or less conducive to the appearance of psychiatric disorders (Yu, Teixeira, Mahadevia, Huang, Balsam, Mann, Gingrich & Ansorge, 2014), supported by its essence, the phenomenality of life, as evidenced by itself, enables passing from the approach of objectivity to that of subjectivity so in it are found the laws that revolve it completely: with the phenomenological reversal life is reborn in its essence and the essence is reborn with it.…”
Section: Affectivity and Interdisciplinaritymentioning
confidence: 99%